A Practical View of In-Gel Gelatin Zymography of Matrix Metalloproteinases 2 and 9 in Cardiac Tissue - Fujimori, Anderson Seiji Soares [UNESP]; Polegato, Bertha Furlan [UNESP] (Springer Nature, 2025)
In-gel zymography is a technique used to evaluate hydrolytic enzymes through SDS-PAGE gel electrophoresis, incorporating specific substrates in a quantitative and qualitative manner. This method is simple, inexpensive, and easy to validate and reproduce. In this chapter, we review the procedure for conducting classical gelatin in-gel zymography, which uses gelatin as a substrate to evaluate matrix metalloproteinases 2 and 9, also known as gelatinases. The technique is versatile and can be performed on various biological materials, including plasma, tissues, and cellular extracts.